Response of mineral mixture, prajana and GnRH on serum biochemical constituents and conception rate in anoestrus buffalo - SINGH, A P; SAH, R S; SINGH, R B; AKHTAR, M H; ROY, G P; SINGH, C; KUNJ, VIVEK (The Indian Journal of Animal Reproduction, 2023)
The serum biochemical constituents (calcium, inorganic phosphorus, total serum protein, blood glucose and alkaline phosphatase) concentration in cycling buffaloes were significantly (P < 0.05) higher than non cycling buffalo. Out of30 anoestrus buffalo cows treated with supplevite -M , 14 ( 16.66%) showed estrus after 30 days treatment, IO buffalo (71.42%) conceived. Out of 32 buffalo heifers 24 were anoestrus and the 8 were under normal cyclic. The anoestrus animals were treated with supplevite-M, at the rate of25 gm/day per animal twice daily for 30 days. The blood biochemical profile ofnormal cycling as well as treated animal was done on 0, 15, and 30th day. No significant difference was noted in serum biochemical constituents in cycling animal while in treated anoestrus animal all the parameters studied and found to be significant.